The democracy manifesto a dialogue on why elections need to be replaced with sortition - Waxman, Wayne (Lexington Books, 2022)
"Elections are not the solution to political crisis, they're the problem. In lively dialogue form, The Democracy Manifesto explains why elections are anti-democratic and should be replaced with government in which decision-makers are randomly selected from the population at large"--